Gender Discourse Analysis of Cyberfeminism's Resistance to Women's Marginalization on the Magdalene.co Page - Rina Rohmatun Hidayah (Journal of Gender and Millennium Development Studies, 2024)
This study describes the discourse of resistance to the marginalization of women's roles on the Magdalene.co website. The existence of new media makes every individual or social, cultural, economic, and political group continue to actively try to interact with new media either as a means of communication or as an effort of empowerment and liberation. This research describes the discourse of resistance to the marginalization of women's roles on the Magdalene.co website. This research uses Norman Fairclough's critical discourse analysis and is strengthened by literature searches. The discourse in this research is reviewed using three levels, (1) micro level, at this level researchers conduct text analysis. (2) meso level, the analysis of the text production process is carried out by interviewing readers of the Magdalene.co article. (3) macro level, namely sociocultural practices, researchers conducted a literature study as a form of seeing the relationship between the text and the social and cultural context that exists in society. The object of this research has several specific requirements as a limitation of the research domain. Based on data analysis, this study found that Magdalene.co builds a discourse on the marginalization of women's roles as a form of resistance to the marginalization of women's roles.